Pengembangan Manajemen Pendidikan Berbasis ICT (Information and Communication Technologies) Di MTs Plus Nurul Falah Jabres Sruweng - Hidayat, Taufik; Fadjeri, Akhmad; Nurchayati, Anisa Dwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Inadequate use of technology in learning administration results in less than optimal efficiency in terms of time and file searches. There are often problems when it comes to the start of the semester, the end of the semester and the accreditation process related to archiving. The aim of this research is to develop ICT-based educational management in order to achieve the goals of learning by utilizing ICT-based technology. The method used is R&D research with the ADDIE (Analysis, Design, Development, Implementation & Evaluation) development model. This research produced data in the evaluation process with a score of 67.19% in the good category. Then the researchers made improvements according to the validator's suggestions and then carried out another evaluation to get a percentage of 85% in the very good category.